Medical devices incorporating collagen inhibitors - SULLIVAN CHRISTOPHER A; YOO JAMES; ATALA ANTHONY; HODGES STEVE J (2013)
Provided herein are implantable or insertable biomedical devices comprising a substrate and a collagen inhibitor on or in said substrate, and methods of treatment using the same. In some embodiments, the device is a urethral, ureteral, or nephroureteral catheter or stent. Kits comprising the same are also provided.